Apoptotic variants as predictors of risk of oropharyngeal cancer recurrence after definitive radiotherapy. Issue 10 (27th July 2015) - Zhang, Fenghua; Sturgis, Erich M.; Sun, Yan; Zhang, Yang; Wei, Qingyi; Zhang, Caiyun; Zheng, Hongliang; Li, Guojun
<x xml:space="preserve">Abstract</x> Single nucleotide polymorphisms (SNPs) in the promoter region of FAS and FASLG may alter their transcriptional activity. Thus, we determined the associations between four FAS and FASLG promoter variants (FAS1377G>A, rs2234767; 670A>G, rs1800682; FASLG844T>C, rs763110 and 124A>G, rs5030772) and the risk of recurrence of squamous cell carcinoma of the oropharynx (SCCOP). We evaluated the associations between FAS and FASLG genetic variants and the risk of recurrence in a cohort of 1, 008 patients. The log‐rank test and multivariate Cox models were used to evaluate the associations. Compared with patients with common homozygous genotypes of FAS670 and FASLG844 polymorphisms, patients with variant genotypes had lower disease‐free survival rates (log‐rank p < 0.0001 and p < 0.0001, respectively) and an approximately threefold higher risk of SCCOP recurrence (HR, 3.2;95% CI, 2.2–4.6; and HR, 3.1; 95% CI, 2.2–4.4, respectively) after multivariate adjustment. Furthermore, among patients with HPV16‐positive tumors, those with variant genotypes of these two polymorphisms had lower disease‐free survival rates (log‐rank, p < 0.0001 and p < 0.0001, respectively) and a higher recurrence risk than did patients with common homozygous genotypes (HR, 12.9; 95% CI, 3.8–43.6; and HR, 8.1; 95% CI, 3.6–18.6, respectively), whereas no significant associations were found for FAS1377 and FASLG124 polymorphisms. Our findings suggest that FAS670 and FASLG844 polymorphisms modulate the risk of recurrence of SCCOP, particularly in patients with HPV16‐positive tumors. Larger studies are needed to validate these results.